Applications of Iron Oxide Nanoparticles against Breast Cancer. (12th May 2022) - Hosseinkazemi, Hessam; Samani, Saeed; O'Neill, Andrew; Soezi, Mahdieh; Moghoofei, Mohsen; Azhdari, Mohammad H.; Aavani, Farzaneh; Nazbar, Abolfazl; Keshel, Saeed Heidari; Doroudian, Mohammad
Abstract : Breast cancer is the most common cancer diagnosed in women, with an estimated 12% of women in the United States affected during their lifetime. Researchers have demonstrated that early detection, diagnosis, and treatment are pivotal to increasing survival. The advent of nanotechnology has yielded several novel advances and available modern methods within the clinic to detect and treat breast cancer. Inorganic nanoparticles are broadly utilized for cancer diagnosis and therapeutic purposes. Interestingly, these nanoparticles can also be attached to tumor-specific ligands and used to deliver chemotherapeutic or hormonal agents with high levels of tumor selectivity. Iron oxide nanoparticles are one of the most commonly used nanomaterials, which have attracted much attention to detect and treat breast cancers, owing to their superparamagnetic characteristics. Computerized tomography and magnetic resonance imaging (MRI) utilizing iron-based magnetic nanoparticles are promising approaches for the radiological detection of breast cancer. Here, we discuss the roles and recent applications of iron oxide nanoparticles in diagnosing and treating breast cancer.